Concise Reliability for Engineers - Mencik, Jaroslav (IntechOpen, 2016)
Our life is strongly influenced by the reliability of the things we use, as well as of processes and services. Failures cause losses in the industry and society. Methods for reliability assessment and optimization are thus very important. This book explains the fundamental concepts and tools. It is divided into two parts. Chapters 1 to 10 explain the basic terms and methods for the determination of reliability characteristics, which create the base for any reliability evaluation. In the second part (Chapters 11 to 23) advanced methods are explained, such as Failure Modes and Effects Analysis and Fault Tree Analysis, Load-Resistance interference method, the Monte Carlo simulation technique, cost-based reliability optimization, reliability testing, and methods based on Bayesian approach or fuzzy logic for processing of vague information. The book is written in a readable way and practical examples help to understand the topics. It is complemented with references and a list of standards, software and sources of information on reliability.